ANALISIS PERKEMBANGAN COFFEE SHOP SEBAGAI SALAH SATU PERANAN UMKM DI KOTA METRO - Aprizal, Muhammad Rizqi; Rojai, Nur Arif; Haezer, Stave Eben; Irawaan, Ferry (COMMENT: Journal of Community Empowerment, 2024)
This research is qualitative research with a qualitative descriptive method that aims to (1) Find out the characteristics of existing millestone coffee shops in Metro City (2) Analyzing the development of millestone coffee shops as one of the roles of MSMEs in Metro City. This research took 1 informant consisting of from the owner of Millestone coffee shop. The data collection method uses interview techniques, observation and documentation. Data analysis techniques consist of data reduction (data reduction), data display (data presentation), and data conclusion drawing/verification. Based on the results of the analysis and assessment, this research shows that the development of coffee shop millestone as one of the roles of MSMEs in Metro City is sufficient well by proving the percentage results on millestone coffee of 80%.